Relationship Between Sleep Quality and Job Stress of Nurses in Different Shifts Working - Nasrin Fadae Aghdam; Malihe Ameri; Shahrbanoo Goli; Malihe Imeni (Hamadan University of Medical Sciences, 2020)
Introduction: Shift work in the nursing profession can affect occupational performance and sleep quality and lead to impairment in coping with job stress. Regarding the possible differences between sleep quality and job stress of nurses in different work shifts, the purpose of this study was to determine the relationship between sleep quality and job stress of nurses in different work shifts. Methods: Carried out in 2016, this descriptive cross-sectional study, studied 139 nurses being selected through stratified sampling from different wards of hospitals affiliated with Shahroud University of Medical Sciences. Data were collected using demographic questionnaires, Tufts and Anderson job stress questionnaires, and Pittsburgh Sleep Quality Questionnaire. Data were analyzed by SPSS 18 using descriptive statistics and statistical tests of correlation, independent t-test and one-way ANOVA. Results: The mean score of total sleep quality of nurses was 7.04±3.2. The highest mean score belonged to the component of useful sleep duration (1.47±1.11) and the lowest to the component of hypnotic drug consumption (0.42±0.834). Pearson correlation test showed a significant relationship between the mean total score of sleep quality and job stress (r=0.176, P=0.036). There was no significant relationship between sleep quality and job stress in different work shifts (P<0.05). Among demographic variables, only tea consumption had a significant relationship with nurses' sleep quality (P=0.043). Conclusion: Finding the factors related to the sleep quality of nurses seems to be essential. Given the relationship between job stress and sleep quality, the necessary arrangements, including stress management workshops, should be considered by hospital managers to achieve the ultimate goal of providing high quality patient care.